EVALUATION OF NATIVE PASTURE AT THE END OF DRY SEASON ON SUB-DISTRICT OF INSANA IN TTU REGENCY - Y., NESI; ., AOETPAH; RANDU, M. D. S.; NDOLU, D. A. J. (Majalah Ilmiah Peternakan, 2024)
The native pasture of Insana sub-district produces potential forage but the long dry season limited the vegetative production. A study has been conducted to analyse forage production, botanical composition and carrying capacity of the native pasture on site of Gua Bitauni village at the end of dry season. The methods applied were survey, ob- servation and measurement on the spot. The forage production was measured using the Halls method, the botanical composition was analysed using a dry weight rank and carrying capacity was determined using the Voisin formula. The results showed that the fresh and the dry weights of the forage were 1.70 t/ha and 1.59 t/ha, respectively. The botanical composition comprised of grasses 84.64%, legumes 13.42%, and weeds 1.94%. Carrying capacity number was 0.71 AU/ha. As the pasture quality was low it was suggested to introduce legumes and other grass species that have strong roots and resistant to drought.